2015
DOI: 10.1509/jm.14.0244
|View full text |Cite
|
Sign up to set email alerts
|

The Chief Marketing Officer Matters!

Abstract: The Chief Marketing Officer Matters!Marketing academics and practitioners alike remain unconvinced about the chief marketing officer's (CMO's) performance implications. Whereas some studies propose that firms benefit financially from having a CMO in the C-suite, other studies conclude that the CMO has little or no effect on firm performance. Accordingly, there have been strong calls for additional academic research regarding the CMO's performance implications. In response to these calls, the authors employ mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
290
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(317 citation statements)
references
References 63 publications
12
290
0
1
Order By: Relevance
“…The second, larger group of studies uses CMO-related constructs to explain firm outcome variables. Some of these studies examine the relationship between CMO presence and various measures of firm performance (Boyd et al 2010;Germann et al 2015;Nath and Mahajan 2008;Nath and Mahajan 2011), while others link CMO characteristics (e.g., education) to firm-related outcomes (Homburg et al 2014;Wang et al 2015;Wang et al 2016), examine how CMO compensation is related to firm performance (Bansal et al 2016;Kim et al 2016), or consider the influence of CMO presence on marketingrelated decisions (Boyd and Brown 2012;Mintz and Currim 2013). In the small third group of CMO-related studies in the marketing literature, which examines the CMO's situation, Nath and Mahajan (2011) find that several contingencies impact the CMO's influence in the TMT, Engelen et al (2013) identify social capital as one of the drivers of CMO influence, and Nath and Mahajan (2017) identify drivers of CMO turnover.…”
Section: Theoretical Background and Hypotheses Development Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The second, larger group of studies uses CMO-related constructs to explain firm outcome variables. Some of these studies examine the relationship between CMO presence and various measures of firm performance (Boyd et al 2010;Germann et al 2015;Nath and Mahajan 2008;Nath and Mahajan 2011), while others link CMO characteristics (e.g., education) to firm-related outcomes (Homburg et al 2014;Wang et al 2015;Wang et al 2016), examine how CMO compensation is related to firm performance (Bansal et al 2016;Kim et al 2016), or consider the influence of CMO presence on marketingrelated decisions (Boyd and Brown 2012;Mintz and Currim 2013). In the small third group of CMO-related studies in the marketing literature, which examines the CMO's situation, Nath and Mahajan (2011) find that several contingencies impact the CMO's influence in the TMT, Engelen et al (2013) identify social capital as one of the drivers of CMO influence, and Nath and Mahajan (2017) identify drivers of CMO turnover.…”
Section: Theoretical Background and Hypotheses Development Literaturementioning
confidence: 99%
“…While some practitioners see the CMO as a key to success (Gilliatt and Cuming 1986;Hyde et al 2004), others see the position as Bdead^ (Turpin 2012). Two recent surveys show that the CMO position is under considerable pressure (Hoda 2015;Moorman 2015), and the academic literature has long offered a mixed account of CMOs' performance consequences (Germann et al 2015;Nath and Mahajan 2008). The imitation-behavior perspective posits that one way in which firms react to ambiguity concerning a practice's performance impact is to model themselves on their industry peers (Abrahamson 1991).…”
Section: Research Conceptualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Peter Drucker (1954) The recent literature in strategic marketing has centered on marketing's influence in the firm (e.g., Clark, Key, Hodis, and Rajaratnam 2014;Feng, Morgan, and Rego 2015;Germann, Ebbes, and Grewal 2015;Homburg, Vomberg, Enke, and Grimm 2015). The core of this discussion views strategic marketing as a field of study encompassing a focus on organizational,…”
mentioning
confidence: 99%
“…Consequently, one main question is how the accountability of marketing spending can be established in a firm. Scholars have suggested that there is a gap in communication at the highest management levels, and have suggested staffing solutions, i.e., appointing a Chief Marketing Officer (CMO) to the top management team, who can communicate marketing's accountability to CEOs and CFOs (Germann et al, 2015). However, Moorman (2013) reports that demonstrating marketing's value remains a challenge, even for CMOs.…”
Section: Managerial Implicationsmentioning
confidence: 99%